2018
DOI: 10.1186/s13063-018-2693-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing isolated soy protein with flaxseed oil vs isolated soy protein with corn oil and wheat flour with corn oil consumption on muscle catabolism, liver function, blood lipid, and sugar in burn patients: a randomized clinical trial

Abstract: BackgroundThere is controversy regarding whether increasing isolated soy protein (ISP) with or without flaxseed oil (FO), as functional foods, would lead to reduce muscle catabolism and cachexia in burn patients.MethodsOne hundred and eighty-eight patients were assessed for eligibility in this randomized controlled trial. Of these, seventy-three eligible patients (total burn surface area 20–50%) were randomly assigned to three groups, labeled as Control (wheat flour [WF] + corn oil [CO]), ISP + FO, and ISP + C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…Especially in burn patients, gastrointestinal congestion leads to impaired functions of digestion and absorption, which further augments the concern of protein nutrition increasing kidney burden [ 34 ]. However, results from a clinical trial indicate that isolated soybean protein with flaxseed oil or corn oil nutritional support has no significant effect on increasing the kidney burden [ 35 ]. In the current study, we observed slightly increased UA levels after burn injury on days 3, 7, and 14, which were further elevated on days 7 and 14 after blended protein administration, but with no significant difference observed between the three groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Especially in burn patients, gastrointestinal congestion leads to impaired functions of digestion and absorption, which further augments the concern of protein nutrition increasing kidney burden [ 34 ]. However, results from a clinical trial indicate that isolated soybean protein with flaxseed oil or corn oil nutritional support has no significant effect on increasing the kidney burden [ 35 ]. In the current study, we observed slightly increased UA levels after burn injury on days 3, 7, and 14, which were further elevated on days 7 and 14 after blended protein administration, but with no significant difference observed between the three groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein supplementation significantly increased lean body mass, but not muscle strength in burn patients 28 . Isolated soy protein and flaxseed oil also reduced muscle catabolism and increased body weight in burn patients 29 . Dietary supplementation with inulin was also observed to improve weight loss and skeletal muscle atrophy in burned rats, probably due to the modulatory effect of inulin on the gut microbiota, which thereby improved metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…La caída en los niveles de glutamina aumenta el riesgo de infección, la permeabilidad intestinal y la mortalidad, por lo que es importante valorar semanalmente estos niveles (2,11). El soporte nutricional con proteína de soya y aceite de linaza favorece el resultado final del paciente, ya que contiene cantidades elevadas de aminoácidos y omega-3, los cuales ayudan a la desinflamación y la cicatrización de las heridas (13).…”
Section: Requerimientos Específicosunclassified